The role of adipose tissue cell elements in the regulation of the nitroxidergic system and possible ways of pharmacological modulation - Bielenichev, I. F.; Maslennikov, S. O.; Dobrelia, N. V.; Khromov, O. S.; Holovakha, M. L.; Ryzhenko, V. P.; Brek, O. O.; Бєленічев, Ігор Федорович; Масленніков, Сергій Олегович; Добреля, Н. В.; Хромов, О. С.; Головаха, Максим Леонідович; et al. (Запорізький державний медико-фармацевтичний університет, 2024)
system under hypoxia conditions. Materials and methods. The studies were carried out on 30 adult white male Wistar rats. All animals were randomly assigned and divided into groups: a control group (15 rats), type 2 diabetes mellitus (T2DM) was induced in the animals of the second group (15 rats). Isolated fragments of the popliteal arteries (PA) and intrapulmonary artery (IPA) were cleared of perivascular adipose tissue (PVAT-) or left uncleaned (PVAT+) and cut into rings. The simulation of acute hypoxia with further study of medical agents were performed. Results. The PA and IPA with PVAT responded to acute hypoxia with vasoconstriction – an increase in the amplitude of contraction in the first and second phases, and after removing PVAT, they responded with a decrease in the maximum amplitude of contraction by 3.4 times in the 1st phase and an increase in amplitude by 1.8 times in the 2nd phase. Perfusion with Angiolin reduced 2nd phase of HV of the PA and IPA. Adding a combination of Thiotriazoline and L-arginine (1:4) to a solution for perfusion of fragments of arteries of animals with T2DM, causes a significant increase in constrictor reactions in both the 1st and 2nd phases of HV, regardless of presence of perivascular adipose tissue. Conclusions. The presence of PVAT affects the HV of arteries, both in normal and in T2DM. The possibilities of ways of pharmacological modulation of the nitroxidergic system depending on the state of PVAT were determined. Мета роботи – оцінити роль елементів жирової тканини в регуляції параметрів нітроксидергічної системи в умовах гіпоксії. Матеріали і методи. Дослідження здійснили на 30 дорослих білих щурах-самцях лінії Вістар. Усіх тварин рандомно поділили на групи: у першу (контрольну) включили 15 щурів; тваринам другої групи (n = 15) індукували цукровий діабет 2 типу (ЦД2). Ізольовані фрагменти підколінних артерій (ПА) і внутрішньолегеневої артерії (ВЛА) очищали від периваскулярної жирової тканини (ПВЖТ-) або залишали неочищеними (ПВЖТ+) і нарізали на кільця. Моделювали гостру гіпоксію, вивчали ефекти лікарських засобів. Результати. ПА та ВЛА із ПВЖТ+ на гостру гіпоксію реагували вазоконстрикцією – збільшенням амплітуди скорочення в першій і другій фазі, а після видалення ПВЖТ – зниженням максимальної амплітуди скорочення в 3,4 раза в першій фазі, збільшенням амплітуди в 1,8 раза в другій фазі. Перфузія тіотріазоліном майже не впливала на гіпоксичну вазоконстрикцію ПА та ВЛА в ПВАТ+ і знижувала амплітуду в другій фазі гіпоксичної вазоконстрикції в ПВАТ- у контрольних тварин. Перфузія ангіоліном знижувала другу фазу гіпоксичної вазоконстрикції ПA та ВЛА, особливо у ПВЖТ+. Додавання комбінації тіотріазоліну та L-аргініну (1:4) до розчину для перфузії фрагментів артерій тварин із ЦД2 спричиняє достовірне посилення констрикторних реакцій і в першій, і в другій фазах гіпоксичної вазоконстрикції незалежно від наявності периваскулярної жирової тканини.
Роль клітинних елементів жирової тканини в регуляції нітроксидергічної системи та можливі шляхи фармакологічної модуляції
Bielenichev I. F. - ORCID ID: 0000-0003-1273-5314; Maslennikov S. O. - ORCID ID: 0000-0002-7505-8587; Holovakha M. L. - ORCID ID: 0000-0003-2835-9333; Ryzhenko V. P. - ORCID ID: 0000-0003-3466-7148.
Keywords: vasoconstriction; pulmonary artery; type 2 diabetes mellitus; nitrosative stress; eNOS; iNOS; thiotriazoline; angioline; combination of thiotriazoline and L-arginine (1:4); endothelial protection; гіпоксична вазоконстрикція; внутрішньолегенева артерія; цукровий діабет 2 типу; нітрозативний стрес; тіотріазолін; ангіолін; комбінація тіотріазоліну та L-аргініну (1:4); ендотеліопротекція